The significance of consciousness in sports - Joshi, P. (2025)
The sport indeed has all the Physical pursuits to achieve and transcend optimum human performance, the physical exercise and related psychological and physiological aspects attached to the very sport or activity. The other side of playing a sport or undergoing a physical activity is to prepare or perform it consciously ' to be in the present' to live and excel the very moment of action, you lose all the mind chattering being into the game. The science focuses on excelling the performance part of it, when it comes to psychological aspect which is game/ sport specific the being deals with tactical perspective of the game however, the overall being thought spiritual and conscious lack in the process which is likely to make it more precision based to get effortless execution of the movements and sport activities. The conscious efforts are amalgamation of subconscious cumulative practices. The consciousness in sport is less spoken term to hone the skill or tactics , practical aspects of this is meditation which helps an athlete to practise mindfulness and be in the present.